(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to find out the role of the Department of Tourism in the Development of Coastal Tourism Objects in Makassar City. This study used descriptive qualitative research with the number of informants was 5 people. The data analysis technique used data reduction, data presentation, and conclusion making. Then the data was collected through interviews, observations, and documentation studies. The results of this study showed that the role of the Tourism Office in Developing Coastal Tourism Objects in Makassar City was seen from the motivator aspect, facilitator aspect, and dynamic aspect. Judging from the motivator aspect, it was not optimal, from the facilitator aspect, it had not run optimally because the provision of facilities and infrastructure had not been adequate, and from the dynamic aspect of all tourism development on the Tanjung Bayang beach was purely from the Community Empowerment Institute but it had not been realized properly. So it was not able to develop tourism objects optimally. Keywords: Role, development, tourist attraction